2020
DOI: 10.3390/polym12081727
|View full text |Cite
|
Sign up to set email alerts
|

Polymers in the Medical Antiviral Front-Line

Abstract: Antiviral polymers are part of a major campaign led by the scientific community in recent years. Facing this most demanding of campaigns, two main approaches have been undertaken by scientists. First, the classic approach involves the development of relatively small molecules having antiviral properties to serve as drugs. The other approach involves searching for polymers with antiviral properties to be used as prescription medications or viral spread prevention measures. This second approach took two distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 154 publications
0
22
0
Order By: Relevance
“…The first includes the use of biopolymers as carriers of antiviral compounds. The second comprises the use of biopolymers containing antiviral fractions, such as amines, carboxylic acid, sulfates, phenols, among others ( Jarach et al, 2020 ). Although the second has been the focus of relevant research, the first has been shown to be more viable and will be the focus addressed below.…”
Section: Food Packaging and Antiviral Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first includes the use of biopolymers as carriers of antiviral compounds. The second comprises the use of biopolymers containing antiviral fractions, such as amines, carboxylic acid, sulfates, phenols, among others ( Jarach et al, 2020 ). Although the second has been the focus of relevant research, the first has been shown to be more viable and will be the focus addressed below.…”
Section: Food Packaging and Antiviral Actionmentioning
confidence: 99%
“…Most viruses have negative charges due to prototrophic groups (carboxyl, amino, guanidyl and imidazole). Antiviral cations bind to DNA, RNA, through virus membrane fitting channels, affecting their fixation and action ( Jarach et al, 2020 ). For example, the addition of Ag nanoparticles (10–80 nm) to acacia gum had antiviral action on Monkeypox and Tacaribe viruses ( Rogers et al, 2008 ; Speshock et al, 2010 ).…”
Section: Food Packaging and Antiviral Actionmentioning
confidence: 99%
“…The earlier review by Chirkov (2002) suggests that chitosan inhibits viral infections in animal cells, but gives little evidence. However, since then, several studies have reported that chitosan has antiviral activity against human cytomegalovirus strain AD169 and H1N1 influenza A virus (Divya et al, 2017; Jarach et al, 2020). Intranasal preparation of chitosan was administered to BALB/c mice to stimulate the innate immune system against H7N9 Influenza viral infection that is normally highly pathogenic to humans.…”
Section: Antiviral Activity Of Chitosan and Its Derivativesmentioning
confidence: 99%
“…Organic compounds, such as polymers, can be used as coatings [23] or as matrices for composites [34] . Antimicrobial fillers for the polymer coatings include nanomaterials with antimicrobial properties, such as metal compounds [ 34 , 35 ] or graphene-based materials [36] . Metallic coatings as fillers have also produced good results [37] .…”
Section: Design Of Antiviral Coatingsmentioning
confidence: 99%